Chronic alcohol intake abolishes the relationship between dopamine synthesis capacity and learning signals in ventral striatum - Deserno, Lorenz (Eur J Neurosci, 2014)
Drugs of abuse elicit dopamine release in the ventral striatum, possibly biasing dopamine-driven reinforcement learning towards drug-related reward at the expense of non-drug related reward. Indeed, reactivity in dopaminergic target areas of patients with alcohol dependence is shifted from non-drug related stimuli towards drug-related stimuli. Such ‘hijacked‘ dopamine signals may impair flexible learning from non-drug related rewards and thus promote craving for the drug of abuse. Here, we used fMRI to measure ventral striatal activation by reward prediction errors (RPEs) during a probabilistic reversal learning task in recently detoxified alcohol-dependent patients and healthy controls (N=27). The same subjects also underwent FDOPA PET to assess ventral striatal dopamine synthesis capacity. Neither ventral striatal activation by RPEs, nor striatal dopamine synthesis capacity differed between patients and controls. However, the ventral striatal coding of RPEs was negatively correlated with craving in patients. Furthermore, we found a negative correlation between ventral striatal coding of RPEs and dopamine synthesis capacity in healthy controls, but not in alcohol-dependent patients. Moderator analyses showed that the magnitude of the association between RPE coding and dopamine synthesis capacity depended on the amount of chronic-habitual alcohol intake. Using a multimodal imaging approach, this study suggests that dopaminergic modulation of neural learning signals is disrupted in alcohol dependence and this is linked to long-term alcohol intake of patients. Drug intake may thus perpetuate itself by interfering with dopaminergic modulation of neural learning signals in the ventral striatum, thus increasing craving for habitual drug intake.